A transduced living hyaline cartilage graft releasing transgenic stromal cell-derived factor-1 inducing endogenous stem cell homing in vivo - Leong, Wenyan (2013)
Stromal cell-derived factor-1 (SDF-1), also known as a homing factor, is a potent chemokine that activates and directs mobilization, migration, and retention of certain cell species via systemic circulation. The responding homing cells largely consist of activated stem cells, so that, in case of tissue lesions, such SDF-1-induced cell migration may execute recruitment of endogenous stem cells to perform autoreparation and compensatory regeneration in situ. In this study, a recombinant adenoviral vector carrying SDF-1 transgene was constructed and applied to transduce a novel scaffold-free living hyaline cartilage graft (SDF-t-LhCG). As an engineered transgenic living tissue, SDF-t-LhCG is capable of continuously producing and releasing SDF-1 in vitro and in vivo. The in vitro trials were examined with ELISA, while the in vivo trials were subsequently performed via a subcutaneous implantation of SDF-t-LhCG in a nude mouse model, followed by series of biochemical and biological analyses. The results indicate that transgenic SDF-1 enhanced the presence of this chemokine in mouse's circulation system; in consequence, SDF-1-induced activation and recruitment of endogenous stem cells were also augmented in both peripheral blood and SDF-t-LhCG implant per se. These results were obtained via flow cytometry analyses on mouse blood samples and implanted SDF-t-LhCG samples, indicating an upregulation of the CXCR4+(SDF-1 receptor) cell population, accompanied by upregulation of the CD34+, CD44+, and Sca-1+ cell populations as well as a downregulation of the CD11b+ cell population. With the supply of SDF-1-recruited endogenous stem cells, enhanced chondrogenesis was observed in SDF-t-LhCG implants in situ.